التعليم الثانوي يف السودان بني الرؤية والتطبيق: إمكانية إستفادة السودان من التجربة املاليزية = Secondary education in Sudan between vision and implementation: the possibility of Sudan benefits from Malaysian experience / Rasha Mostafa Abdelgadir, Amiratul Munirah Yahaya and Asmaa Mohd Arshad - Mostafa Abdelgadir, Rasha; Yahaya, Amiratul Munirah; Mohd Arshad, Asmaa (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2024)
Education plays a pivotal role in the progress of any nation. The research aims to investigate the vision of secondary education, its implementation between Sudan and Malaysia and how Sudan benefits from the Malaysian experience. The research problem addressed the challenges and obstacles that face the implementation of educational vision. These challenges are a lack of finance, poor educational technologies, and a shortage of technical and administrative staff. The methods of data collection involved library research, government and non-government reports. The technique of analysis used was in-depth descriptive analysis. Descriptive data related to the study were analysed using percentages. The study discovered that 1) it is necessary to connect educational vision, finance and implementation; 2) there should be a connection between education and development in Sudan and a separation of party policies from education; 3) the establishment of an educational strategy in Sudan that includes national identity; 4) raise the salary of school teachers and give them financial and moral motivation to keep their social status; 5) increase the annual budget for education, 6) investment in education to nurture today’s students and tomorrow's leaders through training for Sudan to benefit from Malaysian experiences.